Grain dust explosion numbers steady in 1986 - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
Twenty-one dust explosions were reported in the U.S. according to data compiled by Ralph Regan, FGIS Safety Director, and Robert W. Schoeff, Extension Marketing & Safety Specialist, Kansas State University. This compares to 22 in 1985 and a 10 year average of 21 explosions.
Keywords: Grain dust; Dust explosions